Coverage of harm reduction services and HIV infection: a multilevel analysis of five Chinese cities. Issue 1 (December 2017) - Wu, Qing; Kamphuis, Carlijn; Duo, Lin; Luo, Jiahong; Chen, Ying; Richardus, Jan
Abstract Background Since 2003, a harm reduction program for injecting drug users has been rolled out countrywide in China. It entails services for condom promotion, a needle and syringe program (NSP), and methadone maintenance treatment (MMT). However, it remains unknown if and to what extent the coverage of these services at city level is related to a reduced risk of HIV infection among drug users. Methods We wished to quantify the extent to which city-level characteristics (such as NSP and MMT service coverage) and individual-level determinants (e.g., self-reported exposure to NSP and MMT services, knowledge, motivation, and skills) were associated with the risk of HIV infection among drug users. In 2006, we conducted an integrated serological and behavioral survey among drug users in five cities of Yunnan Province, China (N  = 685), constructing a multilevel logistic regression model with drug users clustered within these cities. Results Drug users who reported having received NSP or MMT services were about 50% less likely to be infected with HIV than those who reported not having received them (OR 0.45, 95% CI, 0.26–0.83 for NSP and 0.48, 95% CI, 0.31–0.73 for MMT). Despite a between-city variation of HIV infection risk (ICC 0.24, 95% CI 0.08–0.54), none of the city-level factors could explain this difference. Individual-level determinants such as perceived risk of infection and use of condoms were not associated with HIV infection. Conclusions Although people who had used NSP or MMT services were less likely to be HIV infected, this study found no relationship between city-level coverage of HIV prevention programs and variations in HIV infection between cities. This may have been due to the low number of cities in the analysis. Future research should include the analysis of data from a larger number of cities, which are collected widely in China through integrated behavioral and serological surveys.